2023
DOI: 10.1029/2022jc018795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Heating on Coastal Upwelling Intensity

Abstract: Upwelling in coastal regions is of particular interest to environmental researchers owing to its crucial role in coastal environmental studies. The process plays a key role in distributing not only heat and salt, but also nutrients and biological products in the upwelling region. Coastal upwelling can be induced for various reasons but generally results from Ekman transport due to alongshore winds (Ekman, 1905).It is essential to quantitatively evaluate the coastal upwelling intensity, which can act as a proxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Furthermore, the fact that the downscaled biogeochemical changes mirror those in the parent ESMs indicates that the use of a single regional model is allowing for better resolution but is not fundamentally affecting our results (note Echevin et al (2020) found that biogeochemical trends were different between global and downscaled models in the Peru upwelling system). Additional impacts to explore include the role of changing freshwater forcing, other macro-and micro-nutrients (e.g., iron), and potential transport-related impacts (e.g., more rapid offshore advection associated with a shoaling mixed layer; Jung & Cho, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the fact that the downscaled biogeochemical changes mirror those in the parent ESMs indicates that the use of a single regional model is allowing for better resolution but is not fundamentally affecting our results (note Echevin et al (2020) found that biogeochemical trends were different between global and downscaled models in the Peru upwelling system). Additional impacts to explore include the role of changing freshwater forcing, other macro-and micro-nutrients (e.g., iron), and potential transport-related impacts (e.g., more rapid offshore advection associated with a shoaling mixed layer; Jung & Cho, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…(2020) found that biogeochemical trends were different between global and downscaled models in the Peru upwelling system). Additional impacts to explore include the role of changing freshwater forcing, other macro‐ and micro‐nutrients (e.g., iron), and potential transport‐related impacts (e.g., more rapid offshore advection associated with a shoaling mixed layer; Jung & Cho, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we excluded the upwelling areas (as shown in black rectangles in Figure 1b) and retained only the SST from non-upwelling regions surrounding them as indicators of AMHW events to avoid potential causal inversion resulting from feedback processes. As the average duration of heatwaves in this study was 11 days, short-term surface heating in the upwelling regions would not significantly alter the temperature at the bottom of the seawater [45]. Therefore, the difference between the density derived from the SST and climatological mean salinity in the upwelling region and the climatological density was utilized as an indicator of seawater stratification during the AMHW event.…”
Section: Methodsmentioning
confidence: 99%
“…the temperature at the bottom of the seawater [45]. Therefore, the difference between the density derived from the SST and climatological mean salinity in the upwelling region and the climatological density was utilized as an indicator of seawater stratification during the AMHW event.…”
Section: Methodsmentioning
confidence: 99%